Pengaruh Hubungan Antar Manusia, Disiplin Kerja Dan Budaya Kerja Terhadap Kinerja Karyawan Produksi Giling 1 Kud Sumber Rejo Unit Skt Kecamatan Sukorejo - Iid Wulan (Journal of Economic, Management and Entrepreneurship, 2023)
This research aims to test the influence of human relations, work discipline and working culture to employee performance (Study on employee Milled production 1 of KUD source Rejo Unit of Sukorejo District SKT). The benefits gained from this study are to provide information or overview of human relations, work discipline and work culture to employee performance.The population of this study is all employees of the KUD source Rejo Unit, Sukorejo district of the author data collection method using the dissemination questionnaire, and documentation. The data analysis used in the study is multiple linear regression. With the results of the study showed that there is a partial influence where the human relations variable has a value of Thitung 0.082 < Ttabel 1.655 with a value of sig. 0.935 > 0.05, the working discipline has a value of Thitung 5.504 > Ttabel 1.655, with Value sig. 0.000 < 0.05, Work culture has a value of Thitung 5.981 > Ttabel 1.655, with the value of sig. 0.000 < 0.05 and the simultaneous influence between the variable human relations, work discipline and work culture to employee performance With the value Sig. 0.05 (0.000 < 0.05) and fcalculate 50,647 > F table 2.67.